THU0050 Microrna-365 inhibits il-1β-induced catabolic factor expression by targeting hif-2α in human primary chondrocytes. (15th June 2017) - Lee, MH; Hong, J-I; Hwang, HS; Son, KM; Kim, HA
Abstract : Background: MicroRNAs, small noncoding RNA molecules, are involved in the pathogenesis of various diseases such as cancer and arthritis. Endothelial PAS domain protein-1/hypoxia-inducible factor-2α (EPAS-1/ HIF-2α) is a catabolic transcription factor that regulates osteoarthritis (OA) cartilage destruction. Objectives: In this study, we examined whether microRNA-365 (miR-365) affects interleukin (IL)-1β-induced expression of catabolic factors in chondrocytes via regulation of HIF-2α. Methods: Total RNA was isolated from normal and OA cartilage tissues and human chondrocytes. miR-365 expression was quantified by TaqMan assay. The effects of miR-365 on HIF-2α and HIF-2α-modulated genes were assessed by quantitative real-time reverse polymerase chain reaction (qRT-PCR), Western blot analysis, and enzyme-linked immunosorbent assay (ELISA). Direct interaction of miR-365 with the 3' untranslated region (UTR) of HIF-2α mRNA was examined using a luciferase reporter assay. Nitrite concentration was measured in culture medium using a Griess assay. Results: miR-365 levels were significantly decreased in human OA cartilage relative to normal cartilage. Overexpression of miR-365 significantly suppressed IL-1β-induced expression of HIF-2α in human articular chondrocytes. Pharmacological inhibition of various IL-1β-associated signaling pathways revealed mitogen-activated protein kinase and nuclear factor-κB as the primary pathways driving IL-1β-mediated decreases in miR-365 and subsequent increase in HIF-2α expression. Using a luciferase reporter assay encoding the 3'UTR of human HIF-2α mRNA, we showed that overexpression of miR-365 significantly suppressed IL-1β-induced up-regulation of HIF-2α. Furthermore, miR-365 overexpression significantly suppressed IL-1β-induced expression of catabolic factors, including cyclooxygenase-2, inducible nitric oxide synthase, and matrix metalloproteinase-1, -3 and -13, and nitric oxide (NO) production in chondrocytes. Conclusions: MiR-365 regulates IL-1β-stimulated catabolic effects in human chondrocytes by modulating HIF-2α expression. References: Yang et al. Hypoxia-inducible factor-2alpha is a catabolic regulator of osteoarthritic cartilage destruction, Nat. Med. 16 (2010) 687–693. Akhtar et al. Haqqi, MicroRNA-27b regulates the expression of matrix metalloproteinase 13 in human osteoarthritis chondrocytes, Arthritis Rheum. 62 (2010) 1361–1371. Park et al. MicroRNA-558 regulates the expression of cyclooxygenase-2 and IL-1beta-induced catabolic effects in human articular chondrocytes, Osteoarthritis Cartilage 21 (2013) 981–989. Acknowledgements: This study was supported by the Basic Science Research Program through the National Research Foundation (NRF) of Korea funded by the Ministry of Education (2014R1A1A2059823 and 2016R1D1A1B03932259). Disclosure of Interest: None declared